PS-042 Parenteral nutrition (PN) in premature infants: risk analysis after redesigning a production process. (24th March 2015) - Salazar, C; Mensa, M; Miana, M; Juncos, R; Ceamanos, S; Lopez, C; Codina, C
Abstract : Background: Prescribing and preparing paediatric PN is an extremely complex processes because of manipulation of small volumes, stability problems, risk of contamination and patient fragility. Therefore, we need to manage the risk of such a delicate process. Purpose: To quantify the risk reduction derived from redesigning the preparation process for parenteral nutrition (PN) for preterm infants, identifying residual risks in the current process and planning measures to solve them. Material and methods: The major changes carried out were e-prescribing and improvements in quality control, by double checking on gravimetric preparations and biochemical control. We used FMEA (Failure Mode and Effect Analysis) to analyse the risk of the process, and a group of four pharmacists and two pharmacy technicians was formed to agree and discuss the critical points in the different phases of the process: prescription, validation, processing, quality control and labelling. Then, we qualified these errors in terms of their probability of occurrence (O), severity (S) and detection capacity (D) in the process, assigning values from 1 to 10, and considering that the severity only depends on the critical point. By multiplying these factors, the criticality index (CI = O × S × D) was obtained. The difference between the previous and current CI processes allowed us to compare the risk management in both processes and prioritise those points which required immediate action. Results: We identified 31 critical points and realised that following the old procedure the CI obtained was 4, 964, whereas it was 1, 715 in the current procedure. Therefore, we achieved an overall risk reduction of 65.5%; of which 25.7% was due to e-prescribing, while 28% and 10.5% would have derived from the incorporation of double supervision in the preparation and biochemical control, respectively. However, there are new risks, mainly due to the management of a computer system (4.4%), for which a procedure manual and a training program have been developed. Furthermore, current process have a remaining risk (nearly 30%), which could be reduced by automating the production process. Conclusion: Improvements mentioned above allowed us to minimise the risk associated with paediatric PN production process. Reference: Bonnabry P, Cingria L, Sadeghipour F, et al . Use of a systematic risk analysis method to improve safety in the production of paediatric parenteral nutrition solutions. Qual Saf Health Care 2005;14:93–8 No conflict of interest.